Iron-cobalt composite material and application thereof in promoting germination and growth of corn seeds under drought stress

By pretreating corn seeds with iron-cobalt composites, the problem of corn germination and growth restriction under drought conditions is solved, and its growth indicators and drought resistance in drought environments are significantly improved.

CN119503898APending Publication Date: 2025-02-25NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411433023.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Under drought conditions, corn seeds germinate slowly and have low vitality. Long-term drought will reduce its stress resistance, making it more susceptible to invasion of diseases and pests, affecting growth and yield.

Method used

Corn seeds were pretreated by iron-cobalt composite materials (CoFe2O4NPs), and the germination and growth of corn seeds were promoted under drought stress by seed soaking.

Benefits of technology

The root length, bud length and related growth indicators of corn seeds in arid environments have been significantly improved, such as germination speed and vitality index, and the drought resistance of corn is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503898A_ABST
    Figure CN119503898A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an iron-cobalt composite material, which comprises the following steps: (1) dissolving oxalic acid in deionized water, heating and stirring to obtain an oxalic acid solution; (2) cobalt salt, ferrous salt and sodium sulfite are dissolved in ionized water, and an iron-cobalt mixed solution is obtained; and (3) adding an oxalic acid solution into the iron-cobalt mixed solution, mixing to obtain a mixture, stirring the obtained mixture in a water bath, filtering after stirring, washing the obtained solid product with water and ethanol in sequence, drying overnight, and transferring the obtained powder into a muffle furnace for calcining to obtain the iron-cobalt composite material. The CoFe2O4NPs synthesized by the method disclosed by the invention has the advantages of simple preparation process, high yield, low cost, better material dispersity and the like. The iron-cobalt composite material is combined with a seed treatment technology, germination and growth conditions of corn seeds under drought stress can be obviously promoted, and the method is easy to operate, obvious in effect, low in cost and easy to popularize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crop planting, and in particular relates to an iron-cobalt composite material and an application thereof in promoting corn seed germination and growth under drought stress. Background Art

[0002] With the intensification of global climate change, the problem of drought is becoming increasingly serious, which has had a profound impact on agricultural production and the ecological environment. Under drought conditions, plants face the challenge of insufficient water supply, resulting in limited growth, reduced yield, and even death. Corn is widely planted worldwide and is one of the world's important food crops. Corn is sensitive to water stress. Under drought conditions, corn seeds germinate slowly and have low vitality. In addition, the insufficient water supply caused by drought will directly affect the normal growth of the plant, limit the development of the root system, and reduce its water absorption capacity. At the same time, the stomata of the leaves are closed to reduce transpiration losses, but it also limits the absorption of carbon dioxide, further affecting photosynthesis. Long-term drought conditions will reduce the stress resistance of corn and make it more vulnerable to pests and diseases. Therefore, improving the drought tolerance of corn and enhancing its ability to survive under extreme climatic conditions is crucial to maintaining its growth, development, yield and quality.

[0003] Seed priming is a simple and effective method to treat seeds with natural or synthetic agents before germination to improve plant stress resistance. Micron materials usually refer to materials with a size of micron, that is, a length between 1-1000 microns (μm). Micron priming technology is an emerging seed priming method that uses micron particles as seed pretreatment agents to promote crop seed germination, growth and improve stress resistance through seed priming strategies.

[0004] The present invention adopts an iron-cobalt composite material to promote the germination and growth of corn seeds under drought conditions, which has important practical significance and application prospects. Through the application of this material, the adverse effects of drought stress on the growth of corn seeds can be effectively alleviated, and the drought resistance of corn can be improved, so as to contribute to ensuring food security and promoting sustainable agricultural development. Summary of the invention

[0005] The primary purpose of the present invention is to provide an iron-cobalt composite material and its application in promoting corn seed germination and growth under drought stress, so as to improve the survival rate and yield of corn under drought stress.

[0006] To this end, the present invention provides the following technical solutions.

[0007] One aspect of the present invention provides a method for preparing an iron-cobalt composite material, the method comprising the following steps: (1) dissolving oxalic acid in deionized water, heating and stirring to obtain an oxalic acid solution; (2) dissolving cobalt salt, ferrous salt and sodium sulfite in ionized water to obtain an iron-cobalt mixed solution; (3) adding the oxalic acid solution to the iron-cobalt mixed solution to obtain a mixture, stirring the obtained mixture in a water bath, filtering after the stirring is completed, washing the obtained solid product with water and ethanol in turn, and drying overnight, and then transferring the obtained powder to a muffle furnace for calcination to obtain an iron-cobalt composite material.

[0008] As a preferred embodiment of the present invention, in step (1), the concentration of the oxalic acid solution is 550-600 mM.

[0009] As a preferred embodiment of the present invention, in step (1), the heating and stirring conditions are: temperature 55-60°C, time 2-3 h.

[0010] As a preferred embodiment of the present invention, in step (2), the concentrations of cobalt salt, ferrous salt and sodium sulfite in the iron-cobalt mixed solution are 200-250 mM, 150-200 mM and 300-350 mM respectively.

[0011] As a preferred embodiment of the present invention, the cobalt salt is cobalt nitrate and / or cobalt nitrate hexahydrate, and the ferrous salt is ferrous sulfate heptahydrate and / or ferrous sulfate.

[0012] As a preferred embodiment of the present invention, in step (2), the water bath temperature is 55-60°C, and the calcination conditions are: temperature 350-400°C, time 1-3 h.

[0013] Another aspect of the present invention provides an application of the iron-cobalt composite material prepared by the preparation method as described above to promote the germination and growth of corn seeds under drought stress.

[0014] As a preferred embodiment of the present invention, the application specifically comprises the following steps: S1: Clean and disinfect corn seeds; S2: Soak corn seeds in iron-cobalt composite solution; S3: The soaked corn seeds were subjected to a germination test under drought stress using the Petri dish method.

[0015] As a preferred embodiment of the present invention, in step S2, the solid-liquid ratio of the corn seeds to the iron-cobalt composite material solution is 1 g: 5-10 mL.

[0016] As a preferred embodiment of the present invention, in step S2, the concentration of the iron-cobalt composite material solution is 20-160 mg / L.

[0017] By means of the above technical solution, the present invention has at least the following advantages: The iron-cobalt composite material prepared by the present invention has a chemical formula of CoFe2O4NPs. The preparation process of the iron-cobalt composite material is simple, cost-effective, has a significant yield, and exhibits good dispersibility. These characteristics give the material potential for application in the agricultural field, especially in promoting the germination and growth of corn seeds under drought conditions. The experimental results show that only 80 mg / L of CoFe2O4NPs can significantly improve the root length, bud length and related growth indicators of corn seeds in arid environments, such as germination speed and vitality index. The simplicity, significant effect and cost-effectiveness of this method make it have wide promotion potential.

[0018] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a scanning electron microscopy image of CoFe2O4NPs prepared according to Example 1; Figure 2 The effects of different concentrations of CoFe2O4NPs on the germination and growth of corn seeds under normal growth conditions in Example 1, wherein (A) is the germination rate; (B) is the bud length and the root length; (C) is the vitality index; Figure 3 The effect of 80 mg / L CoFe2O4NPs on promoting germination and growth of corn seeds under drought stress in Example 1, wherein (A) is the germination rate; (B) is the shoot length and the root length; (C) is the vitality index; Note: The t-test was used for statistical analysis. * represents p<0.05, ** represents p<0.0 1, *** Represents p<0.001. DETAILED DESCRIPTION

[0020] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Unless otherwise specified, the percentage content involved in the present invention refers to mass percentage for solid-liquid mixing and solid-solid mixing, and refers to volume percentage for liquid-liquid mixing.

[0022] Unless otherwise specified, the percentage concentrations referred to in the present invention all refer to final concentrations, which refer to the percentage of the added component in the system after the addition of the component.

[0023] The temperature parameters in the present invention, if not specifically limited, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument.

[0024] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.

[0025] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0026] Example 1: Preparation of Iron-Cobalt Composite Material (CoFe2O4NPs) 600 mM oxalic acid was dissolved in 100 ml deionized water, heated and stirred at 60 °C for 2 h to obtain an oxalic acid solution. Cobalt nitrate hexahydrate, ferrous sulfate heptahydrate and sodium sulfite were dissolved in 100 ml deionized water to obtain an iron-cobalt mixed solution, wherein the concentrations of cobalt nitrate hexahydrate, ferrous sulfate heptahydrate and sodium sulfite in the iron-cobalt mixed solution were 200 mM, 160 mM and 315 mM, respectively. The obtained oxalic acid solution was added to the iron-cobalt mixed solution to obtain a mixture. The obtained mixture was vigorously stirred at 1100 r / min in a 60 °C water bath for 2 h, filtered after the stirring was completed, and the obtained solid product was washed with water and ethanol in turn and dried overnight to obtain a powder. The obtained powder was then transferred to a muffle furnace and calcined at 350 °C for 2 h to obtain the iron-cobalt composite material CoFe2O4NPs.

[0027] Figure 1 The scanning electron microscope image of the obtained CoFe2O4NPs. Figure 1 It can be seen that the CoFe2O4NPs are irregularly cubic in shape. The hydrated particle size of CoFe2O4NPs was measured by dynamic light scattering (DLS) to be 4439.5±174.6654 nm, and the Zeta potential was -3.02±0.193132 mV.

[0028] Application Example 1: Effects of Iron-Cobalt Composite Materials on Germination and Growth of Corn Seeds 1. Preparation of experimental materials Preparation of soaking solution: A certain amount of CoFe2O4NPs synthesized in Example 1 was weighed using an analytical balance and dissolved in deionized water, and ultrasonically dispersed for 20 minutes to prepare suspensions of 20, 40, 80, and 160 mg / L, respectively, as soaking solutions for later use.

[0029] Treatment of test seeds: The corn variety "Jingnuo No. 1" was used as the test material. Select corn seeds with uniform size and full grains, and remove shriveled and damaged seeds. Disinfect the selected corn seeds with 5% sodium hypochlorite for 10 minutes, then rinse with deionized water and use them as test seeds for later use.

[0030] 2. Germination experiment The seeds were soaked in 20, 40, 80, and 160 mg / L CoFe2O4NPs suspensions for 24 h, respectively, with a volume ratio of 1:5 between the mass of corn seeds and the soaking solution. After soaking, the seeds were taken out and rinsed with deionized water, and then placed in a culture dish (15 cm in diameter) with a layer of filter paper. 20 seeds were placed in each culture dish and 3 mL of deionized water was added. Four replicates were set for each treatment group, and the seeds were placed in a dark incubator at 25 °C for germination for 7 days, and the seed germination rate of each treatment group was counted.

[0031] The germination test method under drought stress was consistent with the above, except that the concentration of the soaking solution used was 80 mg / L CoFe2O4NPs (the optimal concentration screened according to the experimental results), the control group was soaked in deionized water, and 3 mL of 15% PEG solution was added to the culture dish of each treatment group to simulate the drought environment.

[0032] 3. Index determination method The germination rate of corn seeds in each treatment was counted, and seeds were considered to have germinated when the sprout length or root length exceeded half of the seeds.

[0033] Use a millimeter ruler to measure the shoot length and root length of the seedlings.

[0034] Seed vitality index = (root length + bud length) × germination rate cm % 4. Results and Analysis 1. Effects of different concentrations of CoFe2O4NPs soaking solution on corn seed germination Figure 2 The effects of different concentrations of CoFe2O4NPs on the germination and growth of corn seeds under normal growth conditions in Example 1, where (A) is the germination rate; (B) is the bud length and root length; and (C) is the vitality index. Figure 2 It can be seen that compared with the blank group, different concentrations of CoFe2O4NPs seed soaking generally accelerated the germination of corn seeds to a certain extent ( Figure 2 A). For both shoot and root biomass and seed vigor index, CoFe2O4NPs showed a dose-effect relationship of promotion at low solubility and inhibition at high concentration. With the increase of concentration, 80 mg / L CoFe2O4NPs treatment significantly increased the shoot and root length of seedlings ( Figure 2B), which increased by 13.6% and 16.5% respectively compared with the control group. When the concentration of CoFe2O4NPs reached 160 mg / L, the shoot length and root length of the seedlings decreased by 3.6% and 7.6% respectively compared with 80 mg / L. At the same time, the 80 mg / L CoFe2O4NPs treatment also significantly increased the seed vitality index ( Figure 2 C), which increased by 11.9% compared with the control group. When the concentration of CoFe2O4NPs reached 160 mg / L, the seed vitality index decreased by 10.3% compared with 80 mg / L. Therefore, within a certain concentration range, CoFe2O4NPs seed soaking treatment can promote the germination and growth of corn seeds. Based on the above results, 80 mg / L was finally selected as the optimal concentration for subsequent experiments.

[0035] 2. Effect of CoFe2O4NPs seed soaking on drought resistance of maize seeds during germination Figure 3 Effects of 80 mg / L CoFe2O4NPs seed soaking on germination rate (A), shoot and root length (B), and vitality index (C) of corn seeds under 15% PEG simulated drought stress. Figure 3 It can be seen that drought stress significantly reduced the germination speed, germination rate, sprout length and root length of corn seeds. After soaking seeds with 80 mg / L CoFe2O4NPs, the 36h germination rate of corn seeds was significantly increased (4.2%). Figure 3 A), bud length (32.4%) ( Figure 3 B) Root length (18.3%) Figure 3 B) and seed vitality index (22.2%) ( Figure 3 C). Therefore, 80 mg / L CoFe2O4NPs seed soaking treatment increased the growth indexes of corn seeds under drought stress, such as germination rate, shoot length, root length, and vitality index, and enhanced the drought resistance of corn seeds under drought stress.

[0036] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an iron-cobalt composite material, characterized in that: The method comprises the following steps: (1) dissolving oxalic acid in deionized water, heating and stirring to obtain an oxalic acid solution; (2) dissolving cobalt salt, ferrous salt and sodium sulfite in ionized water to obtain an iron-cobalt mixed solution; (3) adding the oxalic acid solution to the iron-cobalt mixed solution to obtain a mixture, stirring the obtained mixture in a water bath, filtering after the stirring is completed, washing the obtained solid product with water and ethanol in turn, and drying overnight, and then transferring the obtained powder to a muffle furnace for calcination to obtain an iron-cobalt composite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the oxalic acid solution is 550-600 mM; The heating and stirring conditions are: temperature 55-60° C., time 2-3 h.

3. The preparation method according to claim 1, characterized in that: In step (2), the concentrations of cobalt salt, ferrous salt and sodium sulfite in the iron-cobalt mixed solution are 200-250 mM, 150-200 mM and 300-350 mM, respectively.

4. The preparation method according to claim 1 or 3, characterized in that: The cobalt salt is cobalt nitrate and / or cobalt nitrate hexahydrate, and the ferrous salt is ferrous sulfate heptahydrate and / or ferrous sulfate.

5. The preparation method according to claim 1, characterized in that: In step (2), the water bath temperature is 55-60°C, and the calcination conditions are: temperature 350-400°C, time 1-3 h.

6. Use of the iron-cobalt composite material prepared by the preparation method according to any one of claims 1 to 5 to promote corn seed germination and growth under drought stress.

7. The use according to claim 6, characterized in that: The application specifically comprises the following steps: S1: Clean and disinfect corn seeds; S2: Soak corn seeds in iron-cobalt composite solution; S3: The soaked corn seeds were subjected to a germination test under drought stress using the Petri dish method.

8. The use according to claim 7, characterized in that: In step S2, the solid-liquid ratio of the corn seeds to the iron-cobalt composite material solution is 1 g: 5-10 mL.

9. The use according to claim 7 or 8, characterized in that: In step S2, the concentration of the iron-cobalt composite material solution is 20-160 mg / L.

10. The use according to claim 7, characterized in that: In step S3, the drought stress condition is: 15% polyethylene glycol.